1973
DOI: 10.1055/s-0028-1099507
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF LIGHT UPON QUANTITY AND QUALITY OFMATRICARIA CHAMOMILLAOIL

Abstract: Mlztricaria chamomilla L. plants were grown at various light intensities, under controlled conditions in the phytotron.The reduction of light intensity resulted in a decrease in the number and dry weight of flower heads per individual plant, as well as, the size of single flower head. The decrease was relatively greater with decreasing light intensity up to 32 000 ergs/cmYsec.It is conceivable that in general, the higher the light intensity, the higher the essential oil and chamazulene percentage.The total amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Studies on essential oil yield conditioned by shade levels have shown that each species responds differently to light intensity, such as Thymus vulgaris (Li et al, 1996) and Matricaria chamomila (Saleh, 1973), with increased essential oil yield when grown under intense light. Anethum graveolens (Halva et al, 1992), Salvia oficinalis (Li et al, 1996) and Pothomorphe umbellata plants gave higher essential oil yield when cultivated under shade.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on essential oil yield conditioned by shade levels have shown that each species responds differently to light intensity, such as Thymus vulgaris (Li et al, 1996) and Matricaria chamomila (Saleh, 1973), with increased essential oil yield when grown under intense light. Anethum graveolens (Halva et al, 1992), Salvia oficinalis (Li et al, 1996) and Pothomorphe umbellata plants gave higher essential oil yield when cultivated under shade.…”
Section: Resultsmentioning
confidence: 99%
“…The higher solar radiation and the whole lightness activate the accumulation of essential oils in Lippia alba (Verbenaceae), Baccharis trimeria (Asteraceae), T. vulgaris: the higher photosynthetically active solar radiation activates the synthesis of the products of photosynthesis, whereof essential oils as the secondary plant metabolites are biosynthesized Gosselin, 1995, 1996;Sangwan et al, 2001;Silva et al, 2006). However, some facts suggest that higher lightness can reduce the accumulation of essential oils in Anethum graveolens (Apiaceae), Salvia officinalis (Lamiaceae), Potomorphe umbelata (Piperaceae) (Saleh, 1973;Halva et al, 1992;Mattana et al, 2010). Our study showed that PAR April-July significantly positively influenced the yield of the essential oils in C chemotype of T. pulegioides (r = 0.89, p < 0.05) ( Table 3).…”
Section: Effects Of Meteorological Factors On Quantitative Compositiomentioning
confidence: 94%
“…Estudos sobre o rendimento de óleo, a partir de plantas condicionadas por níveis de sombra, demonstraram que cada uma das espécies responde diferentemente à intensidade de luz, tal como Thymus vulgaris (LI;POTTER, 1996) e Matricaria chamomila (SALEH, 1973), apresentando aumento do rendimento de óleo essencial quando cultivadas sob luz intensa (a pleno sol). Anethum graveolens (HALVA; CRACKER; SIMON, 1992), Salvia oficinalis (LI; CRACKER; POTTER, 1996) e Pothomorphe umbellata apresentaram maior rendimento de óleo essencial quando cultivadas sob sombra.…”
Section: Resultsunclassified